Afrikaans: język, w którym spotykają się ideologia i językoznawstwo - Hamans, Camiel (Scripta Neophilologica Posnaniensia, 2021)
This paper summarizes the discussion about the origin and the status of Afrikaans. Two schools appear to be opposed to each other: the philological school and a creolistic view. The philological school tried to demonstrate with meticulous research of sources that Afrikaans is a full daughter of 17th century Dutch, which set foot ashore with van Riebeeck in 1652 at the Cape of Good Hope. Linguists who thought of a pattern of creolization in the formation of Afrikaans point to the influence of the languages of slaves brought to South Africa and to the influence of the original inhabitants, the Khoi and the San. This contribution mainly outlines the ideological background of these two schools of thought. For the philological school this is the system of Apartheid, while for the Creolist view the emphasis is more on decolonization.